(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
The current market produces an environment of constant change, a panorama that has affected retail dealers. This study analyzed four supermarkets located in the city of Entre Rios in Minas Gerais, Brazil. The choice of these stores is justified because the city’s mobile population is increasing due to the implantation of a metallurgical plant close to the city limits. The main objective was to identify, from the point of view of the management from these four supermarkets, which variables take part in the composition of their marketing mix strategies. More specifically, the idea was to: 1) identify and analyze the composition of the marketing mix of the organization; 2) identify if there are strategies of customer relationship being implemented; and 3) identify if there are differences amongst the strategies of the supermarkets. Intentionally chosen, the managers of these supermarkets were interviewed using a semi[1]structured questionnaire. The interviews were recorded and transcribed for future analysis. Besides the interviews, selling points were observed, permitting the elaboration of a comparison of the supermarkets. It was not possible to perceive the use of similar strategies in the elaboration of the marketing mix, since the marketing strategies regarding customer relationships were applied with restriction, especially in one of the analyzed supermarkets.